2018
DOI: 10.3389/fnins.2018.00825
|View full text |Cite
|
Sign up to set email alerts
|

Role of Prenatal Hypoxia in Brain Development, Cognitive Functions, and Neurodegeneration

Abstract: This review focuses on the role of prenatal hypoxia in the development of brain functions in the postnatal period and subsequent increased risk of neurodegenerative disorders in later life. Accumulating evidence suggests that prenatal hypoxia in critical periods of brain formation results in significant changes in development of cognitive functions at various stages of postnatal life which correlate with morphological changes in brain structures involved in learning and memory. Prenatal hypoxia also leads to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 278 publications
(334 reference statements)
2
120
2
1
Order By: Relevance
“…These epigenetic mechanisms may interfere with the gene expression during the early prenatal period the consequences of which are manifested in postnatal life. Indeed, prenatal stress and hypoxia in critical periods of brain development via genetic and epigenetic mechanisms result in significant changes of cognitive functions and increases the risk of neurodegeneration in later life [ 86 , 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…These epigenetic mechanisms may interfere with the gene expression during the early prenatal period the consequences of which are manifested in postnatal life. Indeed, prenatal stress and hypoxia in critical periods of brain development via genetic and epigenetic mechanisms result in significant changes of cognitive functions and increases the risk of neurodegeneration in later life [ 86 , 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of such risk factors is the formation of aberrant neural circuits under the influence of genetic and/or environmental factors (Kovács et al, 2014;Axelrud et al, 2019). Recently, it was reported that prenatal hypoxia (Nalivaeva et al, 2018) and low weight at birth (Heinonen et al, 2015) may be among these factors determining the brain development trajectory as well as the risk of AD. Such conditions can be caused by preterm birth (including 1st degree preterm birth, which usually is not accompanied by cognitive deficits) as well as by trophic insufficiency during gestation owing to a number of causes (Lesuis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Perinatal and prenatal insults are major risk factors for infantile epilepsy [29]. The proposed pathophysiological mechanism is that hypoxia-ischemia that can have deleterious effects on the vulnerable regions of the developing brain lead to substantive injuries that could affect not only seizure threshold but also cognition [30]. Studies have also explored the mechanisms underlying neuronal injury, which could be a cause of epilepsy; rst, hypoxic-ischemic encephalopathy (HIE) initially affects various processes that potentially contribute to energy failure and loss of mitochondrial function, including brain edema, membrane depolarization, increased levels of neurotransmitter release and uptake inhibition, and increased levels of intracellular calcium (which can cause the initiation of further pathological cascades) [31].…”
Section: Resultsmentioning
confidence: 99%